1999
DOI: 10.3109/13550289909029484
|View full text |Cite
|
Sign up to set email alerts
|

Detection of JC virus DNA in peripheral blood cell subpopulations of HIV-1-infected individuals

Abstract: While it has been suggested that JC virus (JCV) migrates in B-lymphocytes from the kidney to the central nervous system where it initiates demyelination, this phase of JCV pathogenesis has not been systematically explored. To determine the peripheral blood cell subpopulation(s) infected with JCV, monocytes, granulocytes, and T and B lymphocytes from HIV-1-infected individuals and uninfected controls were puri®ed by¯ow cytometry. JCV DNA could be detected by PCR ampli®cation in all of these cell subpopulations.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
20
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 22 publications
3
20
0
Order By: Relevance
“…JCV is rarely found in the peripheral blood of normal persons (19,(21)(22)(23). JC viremia occurs in the setting of immunosuppression, and JCV DNA has been detected in the blood of HIV ϩ patients with or without PML who have CD4 ϩ cell counts below 200/l (19, 21, 24 -26).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…JCV is rarely found in the peripheral blood of normal persons (19,(21)(22)(23). JC viremia occurs in the setting of immunosuppression, and JCV DNA has been detected in the blood of HIV ϩ patients with or without PML who have CD4 ϩ cell counts below 200/l (19, 21, 24 -26).…”
Section: Resultsmentioning
confidence: 99%
“…JC viremia, however, is usually not detectable in immunocompetent individuals (19,21,22). The mechanisms that contain JCV replication in normal individuals are not well understood.…”
Section: Discussionmentioning
confidence: 99%
“…The JCV DNA load in the peripheral blood mononuclear cells (PBMC) is very low, between 10 and 90 copies of JCV/g of PBMC DNA (16), and becomes detectable only after PCR amplification and the application of hybridization techniques. JCV has also been detected in cellfree plasma (7,16,17). A recent report has demonstrated that JCV sticks to the surfaces of blood cells rather than productively infecting them (30).…”
mentioning
confidence: 91%
“…13 Thus, when JC virus is detected in the blood, it is more often in the peripheral blood mononuclear cells (PBMC) than than as cell-free virus in the plasma. 12,14,15 To determine whether natalizumab acts only on JC virus or whether its effects would be less specific, we assessed the cellular Finally, to determine whether the findings obtained in the natalizumab-treated cohort would be specific to natalizumab, we assessed all the parameters described above in a control cohort of multiple sclerosis patients treated with interferon beta.…”
Section: Introductionmentioning
confidence: 99%